2008
DOI: 10.1590/s0021-75572008000600007
|View full text |Cite
|
Sign up to set email alerts
|

Farmácias domiciliares e sua relação com a automedicação em crianças e adolescentes

Abstract: Objective: To investigate the contents of home medicine chests and their relationship with self-medication in children and adolescents in the towns of Limeira and Piracicaba, SP, Brazil.Methods: This is a descriptive population study based on a home survey of a simple random sample from both towns, comprising 705 households from census sectors selected by means of cluster sampling. Inclusion criteria: age ≤ 18 years; an obligatory interview with at least one guardian; inventory of medicines kept at home; and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

4
10
0
16

Year Published

2011
2011
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 8 publications
4
10
0
16
Order By: Relevance
“…Older people may be at greater risk for diversion because of declining cognition, dependence on caregivers and economic hardship, making this an important issue for providers to be aware of when prescribing opioids to older patients. These findings, coupled with prior research showing that older adults are known to store their medications in insecure locations [22] and that opioid use is increasing nationally [23] supports future efforts to determine whether and to what extent older adults constitute an important route for opioid diversion.…”
Section: Discussionsupporting
confidence: 67%
“…Older people may be at greater risk for diversion because of declining cognition, dependence on caregivers and economic hardship, making this an important issue for providers to be aware of when prescribing opioids to older patients. These findings, coupled with prior research showing that older adults are known to store their medications in insecure locations [22] and that opioid use is increasing nationally [23] supports future efforts to determine whether and to what extent older adults constitute an important route for opioid diversion.…”
Section: Discussionsupporting
confidence: 67%
“…Studies had also reported that adolescents had access to the home medicine cabinet26 or obtained their medicines from their parents 5. Moreover, parents and pharmacists can probably influence adolescents on the appropriate use of drugs as the majority of our students reported to be self-medicating on their recommendation.…”
Section: Discussionmentioning
confidence: 88%
“…The majority of expatriates residing in UAE come from developing countries where pharmacists often dispense antibiotics without prescriptions 4,34. Consequently, as many of our expatriate adolescents appeared to be successful in obtaining antibiotics, it may be due to easy accessibility to stocks at home16,25,26 (bought from their own home countries or from community pharmacies in UAE30,31) or “leftover” antibiotics from previous prescriptions 26. Inappropriate self-medication with antibiotics and the overall volume of antibiotic consumption in the community have serious implications in the development of antibiotic resistance.…”
Section: Discussionmentioning
confidence: 99%
“…A maioria dos medicamentos encontrados nos domicílios foi dos gêneros anti-hipertensivo, hipoglicemiante oral e diurético, pois o fator de inclusão do estudo é que o usuário seja portador de alguma doença crônica, como HAS e DM. Entretanto, um outro estudo realizado nos municípios de Limeira e Piracicaba no estado de São Paulo com amostra aleatória simples, apontou a presença mais frequente de analgésicos/antipiréticos e antibióticos para uso sistêmico nos domicílios 20 . Diabetes Mellitus e Hipertensão Arterial Sistêmica fazem parte de uma realidade preocupante, com um percentual de 22,3% a 43,9% da população adulta brasileira apresentando a ocorrência de HAS 21 e segundo estimativas da Organização Mundial de Saúde (OMS), o número de portadores de DM no ano de 2000 no mundo era de 177 milhões, no ano de 2014 cerca de 350 milhões de pessoas sofrem DM 22,23 .…”
Section: Discussionunclassified